Acute effect of inhibitory kinesio tape on range of motion, dynamic balance, and gait in athletes with hamstring shortness. (December 2022) - Fereydounnia, Sara; Shadmehr, Azadeh; Salemi, Parsa
Abstract: Objective: The goal of the present study was to investigate the acute effects of kinesio tape on range of motion (ROM), perceived stiffness, and kinetic parameters in athletes with hamstring shortness. Methods: Fifteen athletes with bilateral hamstring shortness were divided randomly into intervention (inhibitory application of kinesio tape plus static stretching) and control (static stretching) groups. Outcome measures were straight leg raise (SLR), active knee extension (AKE) tests for ROM, visual analogue scale (VAS) for perceived stiffness and kinetic parameters which are recorded and calculated by Moticon SCIENCE insoles during four functional performance task of single leg stance (SLS), slow and fast walking and running. Results: ROM, stiffness, and kinetic parameters examined with insoles during SLS and walking tasks changed in both the intervention and control groups (P < 0.05). Furthermore, study groups were different in some variables. The increase in ROM in SLR test and the decrease in perceived stiffness in the intervention group were more evident than in the control group (P = 0.03 and P = 0.001, respectively). There was no difference between the intervention and control groups for the variables in SLS test, slow and fast walking, and running tasks, except for the mean swing duration (MSWD) (P = 0.002) in fast walking. Conclusion: The static stretching alone and the kinesio tape plus static stretching could change many of the kinetic parameters during walking and balance tasks, but the rate of these changes were more significant with kinesio tape plus stretching compared to the stretching alone. Highlights: Static Stretching (SS) had an immediate effects on walking and balance tasks. Kinesio taping (KT) changed the kinetic parameters examined with insoles. KT plus SS were more effective in terms of increasing ROM and decreasing perceived stiffness than the SS alone.